The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00705-020-04911-0
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of genomic diversity of SARS-CoV-2 in different geographic regions of India: an endeavour to classify Indian SARS-CoV-2 strains on the basis of co-existing mutations

Abstract: Accumulation of mutations within the genome is the primary driving force in viral evolution within an endemic setting. This inherent feature often leads to altered virulence, infectivity and transmissibility, and antigenic shifts to escape host immunity, which might compromise the efficacy of vaccines and antiviral drugs. Therefore, we carried out a genome-wide analysis of circulating SARS-CoV-2 strains to detect the emergence of novel co-existing mutations and trace their geographical distribution within Indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 54 publications
4
55
1
Order By: Relevance
“…A number of convergent findings suggest de-mono-ADP-ribosylation of STAT1 by the SARS-CoV-2NSP3 as a putative cause of the cytokine storm observed in the most severe cases of COVID-19. Also, one deletion (at 28245 bp) was present in 10 samples (AF: 6%) in ORF8, a potentially important gene for viral adaptation to humans 44 Sarkar [ 60 ] Research article India 837 Indian SARS-CoV-2 strains 33 different mutations; 18 of which these were unique to India: S glycoprotein (L54F, K77M, R78M, D294D, E583D, Q677H), NSP3 (G716I, T749I, A994D, D1121G, S1197R), RdRP (A97V, L329I, G571S, V880I), NSP2 (S301F, G339S), and N (S194L) Non-synonymous mutations were found to be 3.07 times more prevalent than synonymous mutations. The A2a clade was found to be dominant in India (71.34%), followed by A3 (23.29%) and B (5.36%), but a heterogeneous distribution was observed among various geographical regions.…”
Section: Resultsmentioning
confidence: 99%
“…A number of convergent findings suggest de-mono-ADP-ribosylation of STAT1 by the SARS-CoV-2NSP3 as a putative cause of the cytokine storm observed in the most severe cases of COVID-19. Also, one deletion (at 28245 bp) was present in 10 samples (AF: 6%) in ORF8, a potentially important gene for viral adaptation to humans 44 Sarkar [ 60 ] Research article India 837 Indian SARS-CoV-2 strains 33 different mutations; 18 of which these were unique to India: S glycoprotein (L54F, K77M, R78M, D294D, E583D, Q677H), NSP3 (G716I, T749I, A994D, D1121G, S1197R), RdRP (A97V, L329I, G571S, V880I), NSP2 (S301F, G339S), and N (S194L) Non-synonymous mutations were found to be 3.07 times more prevalent than synonymous mutations. The A2a clade was found to be dominant in India (71.34%), followed by A3 (23.29%) and B (5.36%), but a heterogeneous distribution was observed among various geographical regions.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the method presented here does not rely on primer specificity as compared to conventional qRT-PCR [72] and therefore any changes in viral genomes (mutations or deletion) do not impact the pathogen detection. Previous studies have shown active genetic recombination events in SARS-CoV-2 genomes which may reduce the accuracy of conventional qRT-PCR detection and thus the primers should be precisely chosen to address these challenges [31, 7375].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently the delta variant (B. 1.617.2) has been identified with a different sequence and increased transmissibility characteristics [31]. The dynamic changes in SARS-CoV-2 virus genome that have occurred over the period of pandemic, paired with the recent implementation of vaccination programs on a global scale that might further impact variant generation suggests that routine whole genome sequencing of coronavirus genome could be implemented as a vital part of ongoing disease control.…”
Section: Introductionmentioning
confidence: 99%
“…For performing mutational analysis, each of the 25 protein coding regions of circulating SARS-CoV-2 genomes as well as prototype genome (hCoV-19/Wuhan/WIV04/2019) was cut and subsequently translated to amino acid sequence by using TRANSEQ nucleotide-to-protein sequence conversion tool (EMBL-EBI, Cambridgeshire, UK). Next, each of the 25 protein sequences of 2000 SARS-CoV-2 genomes was aligned with the corresponding protein sequence of the prototype strain by using MEGA software (Version X) and observed for amino acid substitutions [17]. [18].…”
Section: Screening Of Mutationsmentioning
confidence: 99%